2021
DOI: 10.1111/vox.13104
|View full text |Cite
|
Sign up to set email alerts
|

Low ferritin levels appear to be associated with worsened health in male repeat blood donors

Abstract: Background and objectives Frequent blood donation depletes iron stores of blood donors. Iron depletion may lead to anaemia, but the health effects of iron depletion without anaemia in healthy blood donors are not well understood. We studied in the FinDonor cohort whether worsening of self‐rated health of blood donors during the study period was associated with biomarkers for iron levels or other self‐reported changes in lifestyle. Materials and methods We included 1416 participants from the cohort who answered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…1 That one of the healthrelated issues may be (donation-induced) low ferritin levels and iron deficiency, has been overlooked until now. Low ferritin levels are associated with worse health 20 and may increase PLT production which causes higher IPF and MPV. 10,11 The observation that metabolic rates of stored PLTs are associated with MPV on the one hand and donor health on the other hand, is supported by others who found a significantly increased MPV in patients suffering from obesity, 21 Type 2 diabetes 22 or coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 That one of the healthrelated issues may be (donation-induced) low ferritin levels and iron deficiency, has been overlooked until now. Low ferritin levels are associated with worse health 20 and may increase PLT production which causes higher IPF and MPV. 10,11 The observation that metabolic rates of stored PLTs are associated with MPV on the one hand and donor health on the other hand, is supported by others who found a significantly increased MPV in patients suffering from obesity, 21 Type 2 diabetes 22 or coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported 7% of adverse reactions were attributable to iron deficiency-related factors, but it is not evident they distinguished iron-related vs. hemoglobin-related effects. Illustrating the methodological challenges detailed by Spencer et al [51 ▪ ], Finnish investigators reported an association between low ferritin and worsening health but with substantial loss to follow-up and significant risk of selection bias [54 ▪ ]. Iron and hemoglobin affect not just donor health but also retention.…”
Section: Impact Of Iron Deficiency On Blood Donor Healthmentioning
confidence: 99%